2009
DOI: 10.5194/acp-9-1-2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of emissions from on-road sources using a mobile laboratory under various driving and operational sampling modes

Abstract: Abstract. Mobile sources produce a significant fraction of the total anthropogenic emissions burden in large cities and have harmful effects on air quality at multiple spatial scales. Mobile emissions are intrinsically difficult to estimate due to the large number of parameters affecting the emissions variability within and across vehicles types. The MCMA-2003 Campaign in Mexico City has showed the utility of using a mobile laboratory to sample and characterize specific classes of motor vehicles to better quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
5
32
0
1
Order By: Relevance
“…Overall, the gas-phase species results indicate a tendency of the model to underestimate the pollutant concentrations. This is in line with the results obtained from mobile laboratory measurements that indicate an underestimation of the official emissions inventory for Mexicali (Zavala et al, 2009). PM proved to be more difficult to simulate correctly, which is a known setback of current CTMs (Russell, 2008).…”
Section: Air Quality Model Performancesupporting
confidence: 87%
“…Overall, the gas-phase species results indicate a tendency of the model to underestimate the pollutant concentrations. This is in line with the results obtained from mobile laboratory measurements that indicate an underestimation of the official emissions inventory for Mexicali (Zavala et al, 2009). PM proved to be more difficult to simulate correctly, which is a known setback of current CTMs (Russell, 2008).…”
Section: Air Quality Model Performancesupporting
confidence: 87%
“…An analysis of the data inputs used for estimating the PM2.5 emissions from mobile sources in the 2005 MNEI indicates that the average vehicle speed and temperature had the highest sensitivity on the MOVES2010a PM2.5 emission factors estimates. In general, PM2.5 emission factors were higher for higher average vehicle speeds, consistent with studies indicating higher PM emission rates observed under high engine load conditions (i.e., vehicle Table 1. speeds) (Kean et al, 2003;Cadle et al, 2007;Zavala et al, 2009b). Similarly, recent studies are consistent with the observation that fine PM emissions increase with engine load for diesel-powered engines and that volatile fraction of fine PM decreases with increasing load (Ziemmann et al, 2002;Kwon et al, 2003).…”
Section: Pm25 Emissionssupporting
confidence: 70%
“…Aerosols influence climate directly by scattering or absorbing a fraction of the incoming solar radiation to cool or warm the atmosphere, and indirectly via their roles as cloud condensation nuclei (CCN) and ice nuclei (IN), by modifying optical properties and lifetime of clouds (e.g., Penner et al, 2001;Zhang et al, 2007). Additionally, scattering or absorbing a fraction of solar radiation by aerosols also increase or decrease photolysis rates in the atmosphere, affecting ozone (O 3 ) formation and atmospheric oxidation capacity Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%